2014
DOI: 10.3389/fnins.2014.00136
|View full text |Cite
|
Sign up to set email alerts
|

Direct reticular projections of trigeminal sensory fibers immunoreactive to CGRP: potential monosynaptic somatoautonomic projections

Abstract: Few trigeminal sensory fibers project centrally beyond the trigeminal sensory complex, with only projections of fibers carried in its sensory anterior ethmoidal (AEN) and intraoral nerves described. Fibers of the AEN project into the brainstem reticular formation where immunoreactivity against substance P and CGRP are found. We investigated whether the source of these peptides could be from trigeminal ganglion neurons by performing unilateral rhizotomies of the trigeminal root and looking for absence of label.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
(127 reference statements)
1
15
0
Order By: Relevance
“…Previously Panneton et al injected neural tracer WGA-HRP into the peripheral anterior ethmoidal nerve (AEN), which is originated from TG and innervate the nasal cavity, and observed labeled afferent fibers in regions near PB L 31 . In a follow-up study, the authors showed that trigeminal rhizotomy resulted in loss of CGRP expressing fibers innervating the PB L 30 . These and other studies have implied a possible direct TG→PB L pathway 29 32 , but did not provide synaptic or behavior evidence to support this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previously Panneton et al injected neural tracer WGA-HRP into the peripheral anterior ethmoidal nerve (AEN), which is originated from TG and innervate the nasal cavity, and observed labeled afferent fibers in regions near PB L 31 . In a follow-up study, the authors showed that trigeminal rhizotomy resulted in loss of CGRP expressing fibers innervating the PB L 30 . These and other studies have implied a possible direct TG→PB L pathway 29 32 , but did not provide synaptic or behavior evidence to support this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested a direct connection between the trigeminal ganglion and the parabrachial complex, circumventing the canonical relay site in the spinal trigeminal nucleus ( Panneton et al, 2006 , Cavanaugh, 2011 , Cavanaugh, 2011 , Panneton and Gan, 2014 ). More recently, Rodriguez and colleagues demonstrated a monosynaptic, trigeminal ganglion to PB connection that is implicated in craniofacial pain ( Rodriguez, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amplified activity of PB neurons is causally related to chronic pain ( Jergova et al, 2008 , Matsumoto et al, 1996 , Uddin, 2018 , Raver, 2020 ) and changes in PB activity contribute even more heavily in models of craniofacial and orofacial pain ( Rodriguez, 2017 ). Significantly, there exists a direct connection from trigeminal ganglion neurons to PB ( Rodriguez, 2017 , Panneton et al, 2006 , Cavanaugh, 2011 , Cavanaugh, 2011 , Panneton and Gan, 2014 ); bypassing the canonical node in the spinal trigeminal nucleus. Thus, PB is strategically placed to process dura inputs, and to be involved in the pathophysiology of migraine.…”
Section: Introductionmentioning
confidence: 99%
“…This rewiring would have to include neuronal plasticity that develops functional connections between non-AEN but nasally-innervating primary afferent fibers and secondary neurons within the MDH. But even if the AEN has a unique afferent input with central projections beyond the trigeminal sensory complex (Panneton and Gan, 2014 ), there must have been a recovery of function in the animals with bilateral sectioned AENs used by Chotiyanonta et al ( 2013 ), since there was a return of the reflex cardiorespiratory responses to nasal stimulation in these anesthetized animals.…”
Section: Discussionmentioning
confidence: 99%